Unravelling the thread of Podarcis omics; insights into the genome and transcriptome of the Cretan wall lizard - Manos Stratakis; Panagiotis Ioannidis; Iliana Bista; Dominic Absolon; Will Eagles; Shane McCarthy; Amy Denton; Petros Lymberakis; Nikos Poulakakis (Genes & Genomics, 2026)
Background Whole genome data are invaluable resources for both conservation and adaptation studies, especially for endemic species, providing insights into the evolution of genes involved in genomic adaptation across different environments. Objective We compare the newly generated genomic and transcriptomic data of the Cretan endemic lizard species Podarcis cretensis to other Podarcis species to obtain an overview of gene family evolution and genome structure within the genus. Methods Comparative genomic and transcriptomic analyses were performed using the newly published genome of P. cretensis . A gene set was predicted using RNA-seq data from 36 samples, comprising three tissues (liver, brain, and muscle) from both male and female individuals across three distinct habitats. Results The main findings revealed that P. cretensis and P. raffonei present the best genome assemblies and the most syntenic among the Podarcis species examined. Moreover, P. cretensis displayed the highest percentage of single-copy genes and the lowest percentage of duplicated genes. These duplicated genes are primarily associated with immune and sensory-related gene families, including chemokines, interleukins, immunoglobulin-like domain proteins, secreted proteins, and vomeronasal type-2 receptors. Conclusions This study deepens our understanding of chromosome structure, gene expression, and genome evolution in the Podarcis genus, representing the most extensive comparative analysis to date. The newly predicted gene set of the insular endemic species P. cretensis offers initial insights into gene expression related to adaptation across environments and tissues. Comparative genomic analyses further revealed gene families potentially involved in environmental adaptation.

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Genomic infrastructure for cetacean research and conservation: reference genomes for eight families spanning the cetacean tree of life - Phillip A. Morin; Bernhard Bein; Chiara Bortoluzzi; Yury V. Bukhman; Taylor Hains; Dorothea Heimeier; Marcela Uliano-Silva; Dominic E. Absolon; Linelle Abueg; Jessica Antosiewicz-Bourget; Jennifer R. Balacco; Robert K. Bonde; et al. (Frontiers in Marine Science, 2025)
Reference genomes from representative species across families provide the critical infrastructure for research and conservation. The Cetacean Genomes Project (CGP) began in early 2020 to facilitate the generation of near error-free, chromosome-resolved reference genomes for all cetacean species. Towards that goal, and using the methods, goals and genome assembly quality standards of the Vertebrate Genomes Project (VGP), we generated 13 new reference genomes across eight of the 14 cetacean families. Additionally, we summarize the genome assembly characteristics for 18 species, including these newly-generated and five published genome assemblies that meet the completeness and quality standards. We infer ancestral linkage groups (ALG) for cetaceans, showing that the ancestral karyotype of 22 ALGs is largely conserved in extant species, except for Ziphiidae, and for Balaenidae and Kogiidae, which exhibit similar independent fusions. Gene annotation, characterization of historical demography, heterozygosity and runs of homozygosity (ROH) reveal important information for conservation applications. By comparing the new reference genomes to previous draft assemblies, we show that the reference genomes have enhanced characteristics that will support and promote scientific research. Specifically, the genomes improve resolution and characterization of repetitive elements, provide validation (or exclusion) of genes linked to complex traits, and allow more complete characterization of gene regions such as the highly complex Major Histocompatibility Complex (MHC) Class I and II gene clusters that are important for population health.